Modern fourier transform infrared spectroscopy - Christy, Alfred A.; Ozaki, Y. (Yukihiro); Gregoriou, Vasilis G. (Comprehensive analytical chemistry, 2001)
This book is the latest addition to the Comprehensive Analytical Chemistry series. The chapters are designed to give the reader not only the understanding of the basics of infrared spectroscopy but also to give ideas on how to apply the technique in these different fields. Since spectroscopy is the study of the interaction of electromagnetic radiation with matter, the first two chapters deal with the characteristics, properties and absorption of electromagnetic radiation. Chapter 3 provides the basis for vibrations in molecules from a classic mechanical point of view. Absorption of infrared radiation by a vibration in a molecule depends on the symmetry of the molecule and the symmetry of the vibrations. However, these symmetry aspects are not usually treated in textbooks on infrared spectroscopy. Therefore, Chapter 4 deals with the symmetry aspects of molecules and illustrates how the reader can determine the vibrations that are infrared active. Chapter 5 describes group frequencies and assignments of infrared band. Chapter 6 is an overview of the instrumentation used to perform the majority of Fourier transformed infrared spectroscopic experiments today. Chapter 7 describes a variety of the so-called hyphenated techniques that combine the use of FT-IR spectroscopy to another analytical technique. Chapter 8 depicts certain applications of FT-IR spectroscopic techniques to basic and industrial research. Specifically, a big portion of the chapter deals with the characterization of polymers and polymeric surfaces whereas the remaining part describes applications to organic thin films and biological molecules. Finally, Chapter 9 deals with some modern analytical methods in infrared spectroscopy. The methods that are described here are again not very common in books on infrared spectroscopy. In this chapter, the subject of two-dimensional correlation spectroscopy (2D-IR) is also discussed. The principles of the technique along with selected examples of the applications of the 2D-IR treatment are presented.